Herpes zoster oticus with multiple cranial nerve involvement: a rare presentation - Talukdar, Jeumon; Harshvardhan, Harshvardhan (International Journal of Medical Research and Review, 2016)
Herpes zoster oticus is characterized by vesicular rash on the concha, EAC and pinna with a lower motor neuron type palsy of the facial nerve. The disease is a result of reactivation of dormant viral particles either in the geniculate ganglion of the Facial nerve or the spiral and vestibular ganglia of the vestibulocochlear nerve. It is a very painful condition which is usually associated with palsy of the Facial (VII) nerve. We report a case of Herpes zoster oticus involving the V, VII, VIII, IX and X cranial nerves.